1983
DOI: 10.1111/j.1365-2125.1983.tb02159.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations and central nervous system effects of the new hypnotic agent zopiclone in patients with chronic liver disease.

Abstract: Eight healthy individuals and seven cirrhotic patients received 7.5 mg zopiclone orally. Two further cirrhotics received 3.75 mg. Plasma concentrations of zopiclone and psychometric tests including reaction time and critical flicker fusion threshold and electroencephalographic tracings were performed at regular intervals after drug administration. Peak plasma levels of zopiclone were similar in the two groups but the time to peak was delayed in the cirrhotics. Plasma zopiclone half‐life was 8.53 +/‐ 0.83 h in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…This drug was chosen because it has previously been shown that the clinical effects, as measured Correspondence: Dr K. S. Channer, Bristol Royal Infirmary, Bristol BS2 8HW, UK. by psychomotor tests, correlate well with the change in plasma concentration (Parker & Roberts, 1983).…”
Section: Introductionmentioning
confidence: 60%
“…This drug was chosen because it has previously been shown that the clinical effects, as measured Correspondence: Dr K. S. Channer, Bristol Royal Infirmary, Bristol BS2 8HW, UK. by psychomotor tests, correlate well with the change in plasma concentration (Parker & Roberts, 1983).…”
Section: Introductionmentioning
confidence: 60%
“…The decrease in zopiclone plasma concentrations may be characterised by a bi-exponential equation of a 2-compartment model [3,22] or by a I-compartment modeJ.f20, 24] In healthy individuals, zopiclone terminal elimination half-life (ty,z) was found to range from 3.5 to 6.5 hours (table II). The elimination half-life of the N-oxide metabolite ranges from 3.5 to 6 hours, whereas that of the N-demethyl metabolite approximates 7 to 11 hours)n]…”
Section: Half-lifementioning
confidence: 99%
“…In patients with hepatic impairment, increases were seen in elimination half-life (8.4 to 8.5 vs 3.5 to 5.3 hours in healthy volunteers), tmax (3.5 to 4 vs 0.5 to 2 hours) and bioavailability (97 vs 80%) Parker & Roberts 1983]. These changes reflect a reduction in the hepatic metabolic clearance of zopiclone in patients with cirrhosis as shown by the decrease in the metabolic ratio of the two main metabolites in patients with impaired hepatic function ).…”
Section: Effects Of Renal and Hepatic Dysfunctionmentioning
confidence: 98%
“…Absorption rates and times to Cmax (tmax) were similar in young (age 20 to 25 years) and elderly (age 65 to 85 years) volunteers; however, in a subgroup of volunteers aged between 74 and 85 years, Cmax values and areas under the plasma concentration-time curves (AUC) w~re increased (values presented graphically, Gaillot et at. Pharmacokinetic parameters of zopiclone after administration of a single oral 7.5mg dose in healthy volunteers (Caille et al 1984: Channer et al 1984Gaillot et al 1983Gaillot et al , 1987Houghton et al 1985;Parker & Roberts 1983;Stanley et al 1985) Parameter Absorption of zopiclone was delayed when the drug was administered to patients in the supine position although this did not have Table II.…”
Section: Absorption and Distributionmentioning
confidence: 99%